The Therapeutic Values of the Programme "Remembering Yesterday, Caring for Today" in Dementia Care - Agnieszka Sikora-Balicka (Institute of Social Affairs of the Pedagogical University of Cracow, 2021)
This article describes the therapeutic values of the project "Remembering Yesterday, Caring in Dementia Care" for people living with dementia. Project was established with European Reminiscence Network partners in the European Union, which also operates in the USA, Canada, Latin America, Australia and India. The programme is based on the use of creative reminiscence and interpersonal interaction in reminiscence work to "[...] rediscover and celebrate one's individuality and social identity". (European Reminiscence). It can help to alleviate loneliness and/or social isolation, improve health and well-being and, in a broader perspective, "make [...] their lives [...] despite old age and, often with disabilities, a dignified and valuable phase of life". (Zych, 2005, p. 53). Keywords: Alzheimer's disease, creative reminiscence in dementia care, dementia/ non-pharmacological therapy, life history, Remembering Yesterday, Caring for Today.   Terapeutyczne wartości programu ,,Pamiętając o Wczoraj, Troszcząc się o Dzisiaj" w opiece nad osobą żyjącą z otępieniem W artykule opisano terapeutyczne wartości programu ,,Pamiętając o Wczoraj, Troszcząc się o Dzisiaj" dla osób żyjących z otępieniem. Projekt powstał z partnerami European Reminiscence Network, która działa nie tylko w krajach Unii Europejskiej, ale również w Stanach Zjednoczonych, Kanadzie, Ameryce Łacińskiej, Australii i Indiach. Program opiera się na użyciu twórczości artystycznej i interakcji międzyludzkiej w pracy z reminiscencją, aby ,,[...] odkrywać na nowo i celebrować własną indywidualność i społeczną tożsamość" (European Reminiscence Network, 2020). Program może pomóc złagodzić samotność i/lub izolację społeczną, a w szerszej perspektywie - czynić życie, mimo starości i często niepełnosprawności, istnieniem godnym a zarazem wartościową fazą życiową (Zych, 2005).